Consciousness and mind - Rosenthal, David M (New York : Clarendon Press, 2005)
This volume gathers together the work of David Rosenthal on the philosophical study of consciousness from the past 20 years and represents his theory of consciousness as higher-order thought. An introduction draws out the connections between the essays and highlights their implications
Explaining consciousness -- Two concepts of consciousness -- Thinking that one thinks -- Intentionality -- Introspection and self-interpretation -- Qualitative consciousness and homomorphism theory -- The independence of consciousness and sensory quality -- Sensory quality and the relocation story -- Sensory qualities, consciousness, and perception -- Consciousness, expression, and interpretation -- First-person operationalism and mental taxonomy -- Moore's paradox and consciousness -- Why are verbally expressed thoughts conscious? -- Consciousness and its expression -- Content, interpretation, and consciousness -- Self-consciousness -- Unity of consciousness and the self
Includes bibliographical references (pages [365]-370) and index
Keywords: Consciousness; Thought and thinking